How Do Individuals With Bipolar Disorder Experience Ecological Momentary Assessment and Mood Monitoring? A Systematic Review and Qualitative Meta-Synthesis - Daljit Purewal; Georgina Shajan; Goldie Momoh; Shireen Patel; Laurence Astill Wright (BJPsych Open)
Aims: Advancements in smartphone technology and wearable devices allow for novel ways to monitor behaviour, mood, and mental state, as well as to develop new interventions. Understanding the perspectives and preferences of individuals with bipolar disorder (BD) is essential for the success of these mood monitoring interventions and for Ecological Momentary Assessment (EMA) as a data collection method.